Peranan Sistem Informasi Akuntansi Berbasis Teknologi Dalam Menyediakan Informasi Untuk Pengambilan Keputusan Manajemen Pada. PT. Astra Otoparts Tbk. Divisi Winteq - Harnengsih, Siti; Indupurnahayu, Indupurnahayu; Hurriyaturrohman, Hurriyaturrohman (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
The role of accounting information system plays a role of providing information about all activities of the company for its use, especially for management and use it as a basis for decision making. The purpose of writing this thesis is to determine whether the information system applied to by PT. Astra Otoparts Tbk. The Winteq division has really provided accurate, timely, understandable and relevant information for management in decesion making . The type of research that the authors use in this study is field research, ie conducting research directly to the company. The data collection of this research is done by direct interview with the user part that is the Deputy Dept Head of Finance & Administration by collecting data related to the issues discussed. This research uses qualitative descriptive method in analyzing data which will give clear and accurate description and answer from the formulation of this research problem. From the discussion of research results found that the accounting information system At PT. Astra Otoparts Tbk. Winteq division has applied technology accounting information system with good and adequate system with integrated system quickly and precisely supported by good technology hence management use output accounting information system for all kinds of decision. This is evident from the availability of information that is needed right when management needs it